Handbook of applications of chaos theory - Skiadas, Christos H.; Skiadas, Charilaos (CRC Press/Taylor & Francis Group, 2016)
In addition to explaining and modeling unexplored phenomena in nature and society, chaos uses vital parts of nonlinear dynamical systems theory and established chaotic theory to open new frontiers and fields of study. Handbook of Applications of Chaos Theory covers the main parts of chaos theory along with various applications to diverse areas. Expert contributors from around the world'show how chaos theory is used to model unexplored cases and stimulate new applications.